The Oil Supplementation in Animal Feed Research Across Indonesia: Research Method to Data Analysis - Erisa Nova Fitrianggi; Mardiati Zain; Montesqrit (Andalasian Livestock, 2025)
Oil supplementation has abundance of benefit for animals due to its fatty acid content. Otherwise, oil supplementation is being limited due to its effect on coating feed in digestive system and lead animal to hardly digest others nutrient. Moreover, with proper treatment, animal may gain immense benefit from it. Much previous research was conducted on giving oil supplementation yet there are many things remain to be addressed. This article investigated the developing of oil supplementation and finding a gap to be filled to encourage the potential of oil supplementation in Indonesia. There are many items shown on this article such as types of oil, variables, level of oil supplementation and protection used. The result showed that in vivo method used more frequently than in vitro method and Lemuru fish oil was used most rather than another type of oil with the level was on 2 and 3%. Types of animals mostly used is sheep with parameters examined was digestibility. Much previous research also showed that many oil supplementation used protection treatment such as saponification. Furthermore, this article showed that there is mostly parameter used and types of animals and variety of oil supplementation in Indonesia.